Hypocortisolemia following unilateral adrenalectomy. (1st June 2022) - Matter, M; Mateev, E; Sykiotis, G; Demartines, N
Abstract: Objective: Unilateral adrenalectomy (UA) is the best option for unilateral functioning and non-functioning adrenal adenomas, localized primary or metastatic carcinomas. Post-operative hypocortisolemia (HC) in Cushing Syndrome is well known, but several studies reported HC after UA for other indications. A systematic full endocrine investigation for all adrenal mass is not systematic and dexamethasone suppression test (DST) is not recommended in non-Cushing functioning tumours. Double secretion (autonomous cortisol co-secretion) is a rare phenomenon. The purpose of the study was to review incidence of postoperative HC in a tertiary centre. Methods: Retrospective study (2012–2020) looking for hypocortisolemia after UA in patients operated for Cushing Syndrome and other endocrine tumours. Pre- and postoperative laboratory findings were reviewed in a total of 115 patients with UA. Patients receiving perioperative dexamethasone (DEX) for nausea and vomiting prophylaxis were included as well. Results: UA (51 right and 64 left) were performed in 47 women and 68 men (mean age 53.5 y.), laparoscopically in 97 (84.3%, 3 converted). UA indications included: Cushing (8), autonomous cortisol secretion (10, in 2 with combined Conn), Conn syndrome (37), pheochromocytoma (24), non-functioning adenoma (10, adrenal carcinoma (3), adrenal metastasis (19) and other diagnosis (4). 18 patients had a preoperative DST (15.7%). Anaesthesia reports revealed that 53/115 patients received DEX. 51/115 patients had a control of postoperative cortisol level. Hypocortisolemia was observed overall in 28/51 patients, by excluding Cushing patients in 24/45, in 19/53 patients who received DEX and in 7/48 in those without DEX. Confusion comes when patients receiving DEX had normal postoperative cortisolemia. Conclusion: The fact that some patients received DEX (ERAS pathway), complicated the interpretation of cortisol levels at postoperative day one (D1). DEX is known to supress the hypothalamic-pituitary-adrenal axis (HPA axis) at D1. Thus, claiming that hypocortisolemia is the result of cortisol co-secretion (adenoma with double secretion), also able to supress the HPA axis, is not possible in patients who received DEX. These results suggests 1) to fully investigate all hormone functions in case of adrenal mass and 2) not administrating DEX in patients undergoing UA, for adequately assessing the HPA axis function postoperatively.